The Truth at Borders: Asylum and the Structure of Inequality - Kennedy, Francesca Anastasia Winona (Glendon Journal of International Studies, 2017)
Abstract: Many states and international organizations based in the West or in Western doctrines claim to dedicate themselves to the safety and fair treatment of refugees, yet it is becoming increasingly clear that these words contradict reality. Protectionist border controls coupled with the criminalization of migrants through gendered and racial discourses perpetuate the danger of being a modern asylum-seeker. In examining this dichotomy, this paper argues that the borders of Western states are sites where global structures of inequality become visible, despite the supposed “liberal” attitude of these states. The securitization of offshore border sites, detention centres and the case of queer migrants are used to support this argument through the treatment of asylum seekers. Résumé : Beaucoup d’Etats et d’organisations internationales basés dans l’Ouest ou dans les doctrines de l’Ouest prétendent qu’ils sont dédiés à la sécurité et le traitement équitable des refugiés, mais il est de plus en plus évident que ces mots contredit la réalité. Les contrôles des frontières protectionnistes complétés par à la criminalisation des migrants par les discours racialisés et genrés perpétue le danger d’être un demandeur d’asile moderne. En analysant cette dichotomie, cet article soutient que les frontières des Etats de l’Ouest sont des sites où les structures mondiales de l’inégalité deviennent visibles, malgré l’attitude « libérale » prétendue de ces états. La sécurisation des sites de frontières offshore, les centres de détention et le cas des migrants queer sont utilisés afin de soutenir cet argument par rapport au traitement des demandeurs d’asile.